Religious Moderation in the Point of Philosophy: Between Tolerance and Dogma - Haryanto, Toat (Jurnal Iman dan Spiritualitas, 2025)
This research focuses on the importance of religious moderation in the pluralistic society of Indonesia, where tolerance and dogma often clash in religious practice. Although religious moderation is widely regarded as an effort to create social harmony, challenges arise when religious dogmas are seen as unquestionable truths. The purpose of this study is to explore how religious moderation can be applied more inclusively through the lens of the philosophy of religion and to find ways to balance tolerance and dogma. This study employs a qualitative approach with a case study design involving in-depth interviews with religious leaders, community figures, and policy document analysis. The findings show that while religious moderation holds the potential to foster social harmony, its application is often hindered by the rigidity of religious dogmas. The contribution of this research is the discovery that the philosophy of religion can provide a more flexible framework for bridging the tension between dogma and tolerance, allowing religious moderation to be more adaptively implemented in a pluralistic society. This research provides new insights into developing a more inclusive and contextual approach to religious moderation, which can strengthen social harmony in Indonesia.